Design of pressure vessels - Gaddam, Subhash Reddy (Boca Raton : CRC Press, 2020)
Pressure vessels are prone to explosion while in operation, due to possible errors in material selection, design and other engineering activities. Addressing issues at hand for a working professional, this book covers material selection, testing and design of pressure vessels which enables users to effectively use code rules and available design softwares. Relevant equation derivations have been simplified with comparison to ASME codes. Analysis of special components flange, bellow and tube sheet are included with their background. Topics on tube bend, supports, thermal stresses, piping flexibility and non-pressure parts are described from structural perspective. Vibration of pressure equipment components are covered as well.
OCLC-licensed vendor bibliographic record.
Keywords: Pressure vessels -- Design and construction; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical